2018 - CSA Monitoring: Tuma La Dalia Climate-Smart Village (Nicaragua) - Bonilla Findji, Osana; Eitzinger, Anton; Andrieu, Nadine; Jarvis, Andrew; Martínez Barón, Deissy; Aguilar, Amílcar (2019)
This dataset contains the files produced in the implementation of the “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Tuma-La-Dalia Climate Smart Village (Nicaragua) in April 2018. This monitoring framework developed by CCAFS is meant to be deployed annually across the global network of Climate-Smart Villages to gather field-based evidence by tracking the progress on: